The politics of land and food scarcity - De Castro, Paolo , 1958- (Earthscan food and agriculture, 2013)
"In recent years the issue of food security has become centre stage in the global agenda. Through a multidisciplinary approach, this book provides an overview of the new global challenges connected with land, food supply and agriculture. It does not simply raise the debate; rather it aspires to move forward the debate that has started with the G20 meetings. "-- Provided by publisher